2021
DOI: 10.1016/j.rbmo.2021.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive senescence impairs the energy metabolism of human luteinized granulosa cells

Abstract: RESEARCH QUESTION: Female age is the single greatest factor influencing reproductive performance and granulosa cells are considered as potential biomarkers of oocyte quality. Is there an age-effect on the energy metabolism of human mural granulosa cells? DESIGN: Observational prospective cohort and experimental study including 127 women that underwent in vitro fertilization cycles. Women were allocated to two groups: a group of infertile patients aged over 38 years and a control group comprising oocyte donors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…Our findings revealed that the expression of genes related to mitochondrial OXPHOS was significantly downregulated in the ovaries of 8-month-old knockout mice as compared to controls, suggesting that disruption of NAD + de novo pathway resulted in mitochondrial dysfunction which was mediated by the suppression of OXPHOS. Our results support the notion that impaired mitochondrial functions lead to ovarian senescence (Cecchino et al, 2021;May-Panloup et al, 2016;van der Reest et al, 2021;Yang, Lin, et al, 2020). Subsequent analysis revealed that deletion of Ido1 or Qprt impaired mitochondria distribution and decreased mitochondrial membrane potential in oocytes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings revealed that the expression of genes related to mitochondrial OXPHOS was significantly downregulated in the ovaries of 8-month-old knockout mice as compared to controls, suggesting that disruption of NAD + de novo pathway resulted in mitochondrial dysfunction which was mediated by the suppression of OXPHOS. Our results support the notion that impaired mitochondrial functions lead to ovarian senescence (Cecchino et al, 2021;May-Panloup et al, 2016;van der Reest et al, 2021;Yang, Lin, et al, 2020). Subsequent analysis revealed that deletion of Ido1 or Qprt impaired mitochondria distribution and decreased mitochondrial membrane potential in oocytes.…”
Section: Discussionsupporting
confidence: 91%
“…Our data demonstrate that the disruption of the NAD + de novo pathway leads to disturbed mitochondrial functions, suppressed granulosa cell proliferation, and decreased oocyte quality, ultimately resulting in reduced fertility. These findings provided further support for the idea that disrupted mitochondrial functions are a key contributor to ovarian senescence (Cecchino et al, 2021 ; May‐Panloup et al, 2016 ; van der Reest et al, 2021 ; Yang, Lin, et al, 2020 ).…”
Section: Discussionsupporting
confidence: 68%
“…" Spindle defects # Blastocyst rate Xu et al, 2019;Nie et al, 2019;Jia et al, 2020;Ma et al, 2015;Emidio et al, 2014;Zhang et al, 2016;Yang et al, 2018;Wang, Jo, et al, 2017;Xing et al, 2021;Wang, Hassold, et al De Bruin et al, 2004;Liu et al, 2017;Müller-Höcker et al, 1996;Rambags et al, 2014;Simsek-Duran et al, 2013;Wilding et al, 2001;Soares et al, 2020;Xu et al, 2019;Dadarwal et al, 2017;Zhang et al, 2016 Pasquariello et al, 2019;Morimoto et al, 2020;Wilding et al, 2001;Steuerwald et al, 2007;Cecchino et al, 2021;Liu et al, 2017;McReynolds et al, 2012;Takeo et al, 2013;Xu et al, 2019;Sugimura et al, 2012;Ben-Meir et al, 2015 Xing et al, 2021;Yang et al, 2018;Ben-Meir et al, 2019 Fusion and fission alterations Mouse Oocyte (old female, Mfn2À/À, Clpp À/À) " Spindle defects # Maturation rate Altered folliculogenesis # Ovarian reserve Udagawa ...…”
Section: Human Mousementioning
confidence: 99%
“…Indeed, several alterations in granulosa/cumulus cells (GC/CC) and FF have been identified in association with aging. Research in AMA women provided evidence that oxidative stress and mitochondrial dysfunction are markers of aging in CC (Ávila et al, 2016; Cecchino et al, 2021; Li et al, 2021; Tatone & Amicarelli, 2013). Imbalance of ROS levels in GC/CC is likely a result of higher levels of ROS (Tatone & Amicarelli, 2013) in parallel with decreased levels of antioxidant enzymes.…”
Section: Age‐related Oocyte Competence Declinementioning
confidence: 99%
See 1 more Smart Citation